Ultraviolet amplified spontaneous emission from self-organized network of zinc oxide nanofibers - Chen, B. J. (2011)
Self-organized zinc oxide (ZnO) nanofiber network with six-fold symmetry was fabricated on ZnO-buffered (0001) sapphire substrate with patterned gold catalyst by vapor-phase transport method. From the ZnO buffer layer, hexagonal ZnO nanorods with identical in-plane structure grew epitaxially along [0001] orientation to form vertical stems. The nanofiber branches grew horizontally from six side-surfaces of the vertical stem along [0110] and other equivalent directions. The aligned network structure constructed a waveguide array with optical gain. Ultraviolet amplified spontaneous emission was observed along the side-branching nanofibers when the aligned ZnO network was excited by a frequency-tripled Nd:YAG laser.